Testimony, trust, and authority - McMyler, Benjamin (New York ; Oxford : Oxford University Press, 2011)
Much of what we know is acquired by taking things on the word of other people whom we trust and treat as authorities concerning what to believe. But what exactly is it to take someone's word for something? What is it to treat another as an authority concerning what to believe, and what is it to then trust this person for the truth? Benjamin McMyler argues that philosophers have failed to appreciate the nature and significance of our epistemic dependence on the word of others.
Title from home page (viewed on Sept. 5, 2011).
Also issued in print format.
Keywords: Testimony (Theory of knowledge)